Kajian Pragmatik pada Kosakata dan Fonetis Bahasa Penderita Afasia Global - Santoso, Nugroho Ponco; Andayani, Andayani; Setiawan, Budhi (citeus, 2018)
Aphasia is a language disorder caused by brain injury. This study aimed at describing how the pragmatic process and forms on words and language phonemes of those suffering from global aphasia. The study is qualitative research using case study approach. The primary data on this study were collected by purposive sampling whose subject was a global aphasia sufferer who had obtained language rehabilitation during one-year period. The secondary data were taken by using in-depth interview with the family, therapist, and subject's neighborhood. The data were analyzed by comparing the in-depth interview result and the field notes of research. The result showed that the individual with global aphasia still had pragmatic abilities, although s/he could produce meaningless words and sounds. In addition, the individual with global aphasia used gesture and intonation to help convey the idea of her/his utterence. The gestures and intonations performed by the individual with global aphasia were nodding and shaking head, and moving hands; while the forms of intonation changes were sudden change in intonation, imitating sounds, and whisper.